Fat‐1 expression alleviates atherosclerosis in transgenic rabbits. Issue 4 (18th January 2022) - Zhang, Chenyang; Wang, Xiaojing; Sun, Suping; Fu, Yu; Wu, Yi; Zhao, Sihai; Fan, Xinzhong; Liu, Enqi
Abstract: Atherosclerosis is the main cause of cardiovascular diseases. The Fat ‐ 1 gene can express the n‐3 fatty acid desaturase, which converts n‐6 polyunsaturated fatty acids (PUFA) to n‐3 PUFAs. The role of n‐3 PUFAs in atherosclerosis is widely debated. This study explored the effect of n‐3 PUFAs on atherosclerosis in rabbits. In this study, atherosclerosis was induced in Fat ‐ 1 transgenic rabbits and their littermate (WT) rabbits by feeding a high‐cholesterol diet containing 0.3% cholesterol and 3% soybean oil for 16 weeks. Plasma lipid, fatty acid and pathological analyses of atherosclerotic lesions were conducted. Fatty acid composition in the liver and muscle showed that n‐3 PUFAs increased and n‐6 PUFAs decreased in the Fat‐1 group. Plasma high‐density lipoprotein cholesterol (HDL‐C) levels were significantly increased in the Fat‐1 group, and the atherosclerotic lesion area of the aortic arch in Fat ‐ 1 transgenic rabbits was significantly reduced. Histological analysis showed that smooth muscle cells (SMCs) in atherosclerotic lesions decreased significantly. In conclusion, n‐3 PUFAs improve atherosclerosis in Fat‐1 transgenic rabbits, and this process may depend on the increase in plasma HDL‐C and the decrease in the amount of SMCs in atherosclerotic plaques.